Cardiovascular risk according to Framingham Score of residents over 30 years of complex Carapongo San Antonio, Lima, Perú - Díaz Orihuela, Sarita Soledad (2019)
Objective: To determine the level of cardiovascular risk using the Framingham Score residents over 30 years ofthe Urb San Antonio-Carapongo - Stage II. Methods: We performed a descriptive study included 62 people overage 30, of San Antonio Urb. The instrument was Framingham score, which consisted of questions and takingblood samples. Results: Of 100% of people polled 59.7% have a low risk, 25.8% followed by a slight risk whichpresents the other hand has 8.1% high risk and only 6.4% have moderate risk. Likewise from the 50-year-oldpeople are at high risk of cardiovascular disease this equates to 8.1% of the surveyed population. On the otherhand the most frequent factors: smoking, 17.7% reported smoking fewer than 10 cigarettes per day, 8.06%presented high total cholesterol also have high blood pressure 6.5% of first grade. Conclusions: The majorityof the population under study has a low risk of heart disease here at 5 or 10 years according to the Framinghamscore, but it is also true that there are lifestyle and risk factors which lead to suffer from these diseases in ourstudy all the people have more than one risk factor that means that if you do not change that lifestyle, it is verylikely to develop coronary heart disease